Reading Plague in Seventeenth-century London. (16th November 2017) - Harding, Vanessa
Summary: Interest in plague and mortality in seventeenth-century London was fed by the weekly and yearly Bills of Mortality, and by the composite or commemorative plague bills issued in epidemic years. Some surviving examples are annotated, suggesting keen engagement with the content. This article identifies one such annotator as the city law-officer and bibliophile, Richard Smyth (1590–1675), and sets this identification in the context of Smyth's personal experience of plague, and of his book-collecting, reading and writing on the subject of plague, demography and vital statistics. Taken together Smyth's activities illuminate the important role that print and text played in shaping responses to a fearsome and recurrent feature of early modern London life.